CACC: A Cooperative Approachto Cache Consistency in WMNs - Xu, Wenzheng; Wu, Weigang; Wu, Hejun; Cao, Jiannong; Lin, Xiaola (IEEE transactions on computers, 2014)
Cooperative caching is a desirable approach to achieve efficient data access in multi-hop wireless networks. Existing cooperative caching algorithms mostly focus on cache placement. Another key issue, cache consistency, has not been adequately addressed. In this paper, we propose CACC, a cooperative approach to maintain cache consistency for wireless mesh networks. CACC combines push and pull by making use of the hierarchical architecture of mesh networks. The key contribution of CACC lies in two techniques that introduce cooperation among network nodes in delivering invalidation reports (IRs) so as to reduce communication cost and tolerate message losses. The first technique, IR integration, buffers and merges IRs at gateway nodes and periodically broadcasts them. The second technique, cooperative IR re-sending, lets intermediate nodes resend missed IR messages upon request. The interval of IR broadcast is optimized to achieve the optimal tradeoff between push and pull. We conduct numerical analysis to find optimal values for different scenarios. We also perform simulation to confirm our analysis results and compare with existing approaches. The results show that CACC can save message cost significantly (50-70 percent).